Calcium Bioavailability and Serum Calcium Level in Pregnant Rats After Administration of Milk-Based Drinks Containing Lactic Acid Bacteria - Nurwati, Yuni; Hardinsyah, Hardinsyah; Marliyati, Sri Anna; Fahrudin, Mokhamad (Jurnal Gizi dan Pangan, 2021)
This study aims to evaluate calcium bioavailability through serum calcium level in pregnant rats treated with two Milk-Based Drinks (MBD) containing Lactic Acid Bacteria (LAB), i.e Lactobacillus Casei Shirota Strain (LcS) drink, and Four Strains Bacteria (FS) (Lactobacillus rhamnosus, Lactobacillus paracasei, Lactobacillus delbrueckii subp. bulgaricus, Streptococcus thermophiles). It was a completely randomized experimental study using 24 Sprague Dawley rats. Rats were divided into one negative control group with a normal nutritional status (A0) and three undernourished groups. The undernourished groups were divided into one positive control group (A1), one group receiving MBD containing LcS group (A2), and another group receiving MBD containing FS (A3). All rats received high protein diets during pregnancy. The intervention was started in early pregnancy (D0) until 19 days of pregnancy (D19). Blood samples were collected at the D0 and D19. No significant differences in food intake were found among the rats in all groups. Administration of MBD containing LAB in A2 and A3 showed significant (p<0.05) increment of calcium bioavailability (30.79±6.88%; 20.44±9.04%). Both MBDs treatment containing LAB showed no significant difference in serum calcium bioavailability (p>0.05). The results suggest that MBDs containing LAB are useful in enhancing calcium bioavailability.